Characteristics of regular exercise habits among people in the northern mountainous regions of Vietnam - Ngoc, Mai Thi Bich; Dao, Le Thi Minh; Chung, Nguyen Dinh (SPORT TK-EuroAmerican Journal of Sport Sciences, 2026)
This study aimed to analyze and compare the characteristics of sports participation behavior among mountainous populations in the Northern, Central, and Southern regions of Vietnam. A sociological survey method was employed to examine and compare physical exercise habits across these regions, focusing on exercise level, temporal characteristics (time and frequency), types and forms of physical activity, as well as participants’ awareness of the meaning and benefits of physical exercise. The total sample comprised 3,429 participants, including 1,842 males and 1,587 females. The research results indicated that the proportion of mountainous populations regularly engaging in physical exercise was relatively similar across the three regions. Participants in all regions tended to practice both modern and traditional sports. However, the content of physical exercise showed statistically significant differences among the regions (p<0.05). In addition, the majority of respondents demonstrated positive and stable motivations for engaging in physical activity. Their perceptions of the meaning and benefits of physical exercise also varied significantly across regions. These findings highlight important considerations for the development and promotion of physical activity programs among mountainous populations in Vietnam.